The Multilateral Fund and China's compliance with the Montreal Protocol - Zhao, J (SAGE Publications, 2002)
International financial assistance can encourage developing countries to deal with global environmental problems, but there is little empirical study of the specific design features most important for success. This article examines the effect of the Multilateral Fund (MLF) on China’s negotiation of and compliance with the Montreal Protocol. Access to the MLF was a major impetus for China’s ratification of the protocol and the government’s procedural compliance. Because it closed major loopholes, the sector-based approach to funding was far more effective than the project-by-project approach, leading to China’s ultimate success in meeting the protocol’s targets to freeze consumption and production of chlorofluorocarbons by 1999 and halons by 2002. China’s experience suggests that effective international financial assistance mechanisms should make continuous fund eligibility contingent on evidence of successful compliance with treaty obligations, target sectors in which manufacturers have limited incentives to meet treaty obligations on their own, and use market-based instruments.